A block mapping strategy for self-recovery in image watermarking - Amrullah, Agit; Ernawan, Ferda (IEEE, 2025)
Digital watermarking technique has become a crucial method for authentication and verification of the ownership of an image. This paper presents a block mapping strategy designed for self-recovery in fragile image watermarking. The proposed method aims to address the challenges of tamper detection accuracy and image recovery quality, maintaining the integrity of digital image. A block mapping strategy is introduced to enhance the quality of image recovery. The proposed block mapping strategy used an average block of 2x2 pixels to generate six MSB recovery bits. Each six MSB recovery bit is randomly embedded into three different blocks. The proposed scheme also embeds two authentication bits within a non-overlapping 2x2 pixel. The proposed scheme also uses the Surrounding Tamper Detection to improve the precision of tamper detection. The watermarked images are evaluated under various malicious attacks to evaluate the proposed block mapping. The results demonstrate that the proposed block mapping strategy achieves a high precision value of 1, and high imperceptibility of recovered images with a PSNR of 44.0529 dB.